(untitled) (Pain medicine, 2016)
The article covers the study of influence of different concentration local anesthetic (4 %, 2 %, 1 %, 0.5 %, 0.25 %) on irritability of nerve fibers in different groups of animals. The optimal concentration and volume of Ultracain DS in cases of сonductive block is determinated.